Effect of the Partial Substitution of Zn with Co, Ni, and Co-Ni on Microstructures and Mechanical Properties of Long-Period Stacking Ordered Dominant Mg-Y-Zn Alloys - Heng Xue; Jinbei Lyu; Fengxue Wang; Hongxin Liao; Jonghyun Kim; Fusheng Pan (Advances in Materials Science and Engineering)
The microstructures of Mg96Y2Zn2, Mg96Y2Zn1Co1, Mg96Y2Zn1Ni1, and Mg96Y2Zn1Co0.5Ni0.5 (at.%) alloys were investigated by XRD, SEM/EDS, and TEM. The α-Mg matrix, the long-period stacking ordered (LPSO) phase, and the bright compounds were observed in the as-cast alloys. The ability of Co to form LPSO phase with Mg and Y is weaker than that of Zn, but it can produce some new intermetallic compounds. The effect of Ni on phase content of alloys was opposite to that of Co. After replacing partial Zn with Co and Ni, the increase in the LPSO phase is more obvious than that of Co or Ni alone to replace partial Zn. The ability to form LPSO phase with Mg and Y atoms in Mg-Y-TM alloys can be ranked as follows: Co-Ni > Ni > Zn > Co. From the point-of-view of mechanical performance, the substitution of Co-Ni for partial replacement of Zn exhibited the best yield strength; the tensile yield strength, ultimate tensile strength, compressive yield stress, and ultimate compressive stress of which were 345 MPa, 453 MPa, 335 MPa, and 470 MPa, respectively. However, the ductility did not improve significantly.